PENGARUH KOMPENSASI, MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA GURU (Study Kasus di SMK Plus Al Maarif Singosari) - nanang tri haryoko; Budi Wahono; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to determine: 1. To determine the simultaneous effect of compensation, work motivation and leadership on teacher performance at SMK Plus Almaarif Singosari. 2. To determine the partial effect of compensation, work motivation and leadership on teacher performance at SMK Plus Almaarif Singosari.The method used in this research is a quantitative research method with a descriptive approach and was carried out by SMK Plus Al Maarif Singosari with a population of 54 teachers. The data collection technique used a questionnaire with measurements using a Likert scale. The data analysis technique used is validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, F hypothesis test, t hypothesis test and determination coefficient test.            The results of this study indicate that: 1. Simultaneously compensation, motivation, and leadership have a significant effect on teacher performance at SMK plus ALMAARIF Singosari. 2. partially compensation, motivation, and leadership have a significant effect on the performance of teachers in SMK plus ALMAARIF Singosari.Keywords: Compensation, Motivation and Leadership.